The effect of the implementation of quick responses indonesia standard (qris) on public purchase interest in the Lama market of Serang City - Chusaeni, Muhammad Faizal; Raehani, Putri; Lutfi, Lutfi; Sa'diyah, Sa'diyah; Wahyudi, Wahyudi (Jurnal Mantik, 2024)
The QRIS implementation system policy is contained in the Board of Governors Regulation Number 21/18/PADG/2019 concerning the Implementation of the Quick Response Code National Standard for payments, which explains that QRIS transactions are directed to be in line with the Banten Provincial Government program, namely SIAP QRIS. Banten region occupies the top 5 positions as the province with the most QRIS users. One of these SIAP QRIS programs is focused on the Lama market of Serang City. A descriptive quantitative method was used in conducting this research. This research also has a limitation, namely in discussing how much influence the QRIS application has on buying interest. It is carried out on the population of Serang City, which has a total of 730,530 people. A sample was drawn using the Slovin formula with an MoR of 10%, namely 100 respondents. This study also aims to prove the influence of applying QRIS on buying interest. The determination of respondents is carried out as one of the instruments, namely using the purposive sampling technique. The results obtained based on field findings and the calculation results show that the Lama market in terms of provision has not been maximized, but the payment method is very reliable. It can be seen in the final calculation results that the variable (x) QRIS application and the variable (y) purchase interest influence 28.3%. In addition, variable (x) and variable (y) show a strong correlation indicated by the acquisition of a Pearson Correlation value of 0.532.